Hypertension in Older People: Part 2 - Franklin, Stanley S. (J Clin Hypertens (Greenwich), 2007)
There is overwhelming evidence that pharmacologic treatment of isolated systolic hypertension (ISH) (systolic blood pressure ≥140 mm Hg and diastolic blood pressure <90 mm Hg) reduces cardiovascular events and extends longevity in the elderly; in the very old (80 years or older), the evidence supports decreased incident stroke and heart failure, but is less convincing in terms of longevity. Thus, the inherent increased risk for ISH vascular events highlights the importance of its control. Importantly, ISH in the elderly, primarily related to large artery stiffness, remains more difficult to control than diastolic hypertension in the young, which is primarily related to increased peripheral vascular resistance. Appropriate lifestyle and pharmacologic intervention is indicated in individuals with systolic blood pressure ≥140 mm Hg in general and ≥130 mm Hg in persons with diabetes or chronic kidney disease. Lifestyle intervention may reduce the need for extensive antihypertensive therapy and minimize associated cardiovascular risk factors. To date, only a small percentage of older ISH patients are being treated to goal. Reaching target systolic blood pressure levels most often requires the use of polypharmacy that includes a diuretic and perhaps specific agents that target arterial stiffness and early wave reflection.